Instructional leadership beliefs among Filipino pre-service teachers - Rudolf T Vecaldo (Institute of Advanced Engineering and Science, 2019)
In the teacher education context, there has been a call to pay attention to the preparation of pre-service teachers for instructional leadership roles necessary in today’s various school reforms. Nonetheless, because the integration of instructional leadership is relatively new in the Philippine teacher education curriculum, there is a dearth of research along with this aspect. With the increasing need for more research on instructional leadership, particularly on Teacher Education Institutions (TEIs), this exploratory study was undertaken. Using an in-depth interview, it examined the instructional leadership beliefs of Filipino pre-service teachers. Twelve (12) graduating pre-service teachers from a public university in Cagayan Province, Philippines became the study participants whose views, insights, and narratives were thematically analyzed. Interestingly, the results of the study revealed that pre-service teachers believe that instructional leadership is shared, learning-focused, a conversation, service-driven, and a pursuit of equity. These deepen the assertion that understanding the instructional leadership beliefs of pre-service teachers would promote instructional interventions that can empower them and advocate a viable instructional leadership framework not only in the Philippine context but in the ASEAN region as well.